The Influence of the Level of Financial Literacy of Village Officials on the Financial Performance of Villages in the Sub-district South Ponrang, Luwu Regency - Peri Herdiansyah; Goso; Antong (LP2M IAIN Palopo, 2025)
This study aims to analyze the impact of financial literacy of village officials, focusing on financial knowledge, financial behavior, and financial attitudes, on the financial performance of villages in Ponrang Selatan District, Luwu Regency. The research design used is quantitative with a survey approach. Data were obtained through the distribution of questionnaires to 60 village officials responsible for managing the finances of their respective villages. The data analysis method used is multiple linear regression. The results show that the financial literacy of village officials, which includes financial knowledge, behavior, and attitudes, both partially and simultaneously, has a positive and significant impact on the financial performance of villages in South Ponrang. Therefore, it is recommended that local governments enhance financial literacy training for village officials. Future research could explore other factors influencing village financial performance and the long-term impact of improving financial literacy.